Dinâmica de spin no comportamento do exciton - Contreras, Jhon (2023)
This thesis presents a study on the spin dynamics of confined excitons under the influence of a magnetic field. Experimental observations reveal unique correlations between Zeeman splitting and spin thermalization, which can be tuned to both temperature and incident light power. The theoretical model, which considers the eventual spin thermalization of bright excitons, qualitatively agrees with the experimental observations and highlights the importance of the exchange interaction. Furthermore, this study goes beyond previous approaches, offering additional insights into spin relaxation and the effects of correlations between bright and dark excitons. Two fundamental conclusions are derived from this work: first, it is shown that the spin dynamics of excitons confined under a magnetic field can be tuned by both temperature and incident power. Second, it is noted that the polarization of the electrons is not appropriate to adjust the experimental curve of the degree of optical polarization, since under the same approximations it is obtained that the optical polarization is zero. These conclusions provide valuable insights for interpreting experimental measurements and guiding future investigations into the spin dynamics of excitons in confinement.